Willingness of female sex workers to use HIV self-testing in Burkina Faso: analysis of cross-sectional respondent-driven sampling data - Cisse, Kadari; Ouedraogo, Henri Gautier; Ky-Zerbo, Odette; Kambire, Dinanibè; Dahourou, Désiré Lucien; Dah, Ter Tiero Elias; Zida, Sylvie; Ki-Toe, Célestine; Dioma, Solange; Sissoko, Fatou; Yugbare, Alexandre; Ouedraogo, Abdoul Ibrahim; et al. (Frontiers in Public Health, 2025)
BackgroundHIV self-testing (HIVST) is an approach that allows individuals to test for HIV and obtain results in their homes or other private settings. It is recommended by the World Health Organization (WHO), particularly for key populations, to help achieve the first 95. The objective of this study was to evaluate the willingness to use HIVST among female sex workers (FSWs) in Burkina Faso.MethodsWe performed a biobehavioral cross-sectional study conducted in five regions in Burkina Faso. FSWs were recruited using the respondent-driven sampling (RDS) method. To evaluate FSW’s willingness to use HIVST, each participant was invited to answer a “Yes” or “No” question: “If you were offered an HIV self-test, would you use it?.” The determinants of willingness to use HIVST were identified using Poisson-modified generalized estimating equation models.ResultsA total of 1,338 FSWs were included in this study. The mean age was 28.1 years (standard deviation: 7.71 years), and 47.9% of FSWs had attended at least secondary school. Nearly 21.1% had good knowledge of HIV transmission modes. One-third (28.8%) of FSWs reported not using a condom during their last sexual intercourse with a non-paying partner. Among the study participants, 89.5% (95% CI: 87.0; 91.6) were willing to use HIVST. The main determinants of FSW’s willingness to use HIVST were being married (adjusted prevalence ratio (aPR): 1.10 (95%CI: 1.01; 1.20) p = 0.034), having first sex at the age greater than 18 years (aPR: 1.14 (95%CI: 1.02; 1.29) p = 0.024), being member of an association (aPR: 1.10 (95%CI: 1.02; 1.18) p = 0.014), and being no current alcohol consumer (aPR: 1.06 (95%CI 1.01; 1.12) p = 0.026).ConclusionThis study revealed a good willingness to use HIVST among FSWs. This is a promising means to increase HIV testing coverage and knowledge of HIV status among FSWs and would then strengthen HIV prevention and care services.